Multi-pages structure for Six Sigma performance matrix based on the technical characteristics of balanced performance and methodology Al-Sigma for measuring corporate performance: Suggestion vision (Journal of Accounting and Financial Studies ( JAFS ), 2013)
Accelerates operating managements in the facilities contemporary business environment toward redefining processes and strategies that you need to perform tasks of guaranteeing them continue in an environment performance dominated by economic globalization and the circumstances of uncertainty attempt the creation of a new structure through multiple pages seek to improve profitability and sustainable growth in performance in a climatefocuses on the development of institutional processes, reduce costs and achieve customer satisfaction to meet their demands and expectations are constantly changing. The research was presented structural matrix performance combines methodology Alsigma in order to improve customer satisfaction significantly between Technology performance balanced with a view to achieving the goals of the business financial and non-financial cross-axes multi for continuous improvement and strengthening of management responsibility and encourage the participation of human resources in achieving measurements of performance objectives.The research found that guided the elements and principles of the matrix of the performance of the Six Sigma related leadership and profitability, management and optimization, sales and distribution, service and growth, human resources and innovation, operational excellence and management of procurement and suppliers will enable the administration to achieve improvement and profitability and processes within the business all the efficiency, effectiveness and economic.